Basic data report on the turbulent spread of heat & matter - McQuivey, R. S. (Raul S.), author; Keefer, Thomas N., author; Shirazi, Mostafa A., author; U.S. Department of the Interior, publisher (Colorado State University. Libraries, 1971)
The purpose of this report is to present the results of an investigation of the turbulent transport properties of heated and salt water jets in an open channel flow. The data were taken cooperatively by the U.S. Geological Survey and the Environmental Protection Agency. The data include measurement of the turbulence characteristics, longitudinal dispersion, and vertical and lateral turbulent diffusion. Three different boundary roughnesses were used in the investigation. The turbulence data includes the intensity of turbulence, Eulerian time scales, autocorrelation function distributions, space correlation distributions in the vertical and horizontal directions and space-time correlation function distributions in the longitudinal direction. Vertical and lateral turbulent diffusion data were obtained downstream from jets of three diameters, at four different jet strengths. Two tracer fluids, heated water and a neutrally buoyant salt solution were used. Only basic data are reported here. The extensive analysis of these results will be the subject of a future publication.
CER71-72RSM-9.
August 1971.
United States Department of Interior Geological Survey, Water Resources Division in cooperation with the United States Environmental Protection Agency, National Thermal Pollution Research Program.
Keywords: Turbidity; Water -- Analysis